Improving livelihoods through goat rearing and commercialisation in Mozambique - International Livestock Research Institute (International Livestock Research Institute, 2013)
Through photographs and captions, this film shares experiences from a 'Small ruminant value chains as platforms for reducing poverty and increasing food security in dryland areas of India and Mozambique' (imGoats) project. Between 2011 and 2013, the imGoats project worked with farmers in Inhassoro District in Mozambique to transform their goat farming and marketing into a commercially-viable activity.